2020
DOI: 10.1111/jan.14592
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of blood glucose control protocol for open heart surgery patients

Abstract: Aims To evaluate the effectiveness of a tailored blood glucose control protocol for postoperative cardiac surgery patients treated in intensive care. Design Retrospective study. Methods Data for the control group (non‐tailored protocol) were collected from medical records at a tertiary hospital in Seoul, Korea between April–July 2015. Data for the experimental group (tailored protocol) were obtained from medical records between April–July 2016. After adjusting the target blood glucose range, eliminating single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Many studies have confirmed the facilitating role of leadership in the process of ICU program implementation and quality improvement [ 45 ]. However, in the process of IIP implementation, researchers seem to pay more attention to the achievement of target blood glucose and the occurrence of complications [ 13 , 33 ]. Few studies have mentioned the role of leadership.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have confirmed the facilitating role of leadership in the process of ICU program implementation and quality improvement [ 45 ]. However, in the process of IIP implementation, researchers seem to pay more attention to the achievement of target blood glucose and the occurrence of complications [ 13 , 33 ]. Few studies have mentioned the role of leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the perceptions of healthcare professionals in the ICU about glucose management have a direct impact on the effectiveness of glucose management in critically ill patients. However, more studies have tended to explore the development of IIPs and the effectiveness of glycaemic control [ 13 , 14 ], few studies have focused on this.…”
Section: Introductionmentioning
confidence: 99%